Development of Game Based Learning Media for Komering Culture (Case Study at Karang Binangun Elementary School) - Ruswita, Istiana; Nasya Fhadila Nurulsyah; Muhammad Afdhaluddin (Universitas Islam Kuantan Singingi, 2025)
The development of Android smartphone technology demands innovation in learning, one of which is through educational games. The Komering culture, as a treasure of South Sumatra, faces the challenges of globalization, which has led to a decline in the younger generation's understanding and appreciation of local cultural heritage. Karang Binangun State Elementary School has integrated Komering language lessons as local content for 6th grade students, but learning still uses conventional methods with textbooks without the development of digital media. This study aims to develop and evaluate Komering culture-based learning media in the form of games to improve local cultural learning in elementary school students. The research uses the Game Development Life Cycle (GDLC) method, which includes the stages of Initiation, Pre-production, Production, Testing, Beta, and Release. The game was developed to cover material on Komering script, language, traditional houses, dances, traditional clothing, and traditional food, and was designed for a single user. The evaluation was conducted through User Acceptance Testing (UAT) involving students and teachers. The results of the study show that the satisfaction level of respondents in the UAT reached 91.88% out of 22 respondents, indicating that the game is very suitable for use as a learning medium. The game has been released and can be accessed via Google Drive for widespread use. This digital learning medium is expected to contribute to the preservation of Komering culture through a modern, interactive, and effective approach.